2019
DOI: 10.1111/jcmm.14655
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation and 2‐oxoglutarate‐dependent dioxygenase inhibition suppress mantle cell lymphoma's cyclin D1

Abstract: The patients with mantle cell lymphoma (MCL) have translocation t(11;14) associated with cyclin D1 overexpression. We observed that iron (an essential cofactor of dioxygenases including prolyl hydroxylases [PHDs]) depletion by deferoxamine blocked MCL cells’ proliferation, increased expression of DNA damage marker γH2AX, induced cell cycle arrest and decreased cyclin D1 level. Treatment of MCL cell lines with dimethyloxalylglycine, which blocks dioxygenases involving PHDs by competing with their substrate 2‐ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…DFX has also been reported to inhibit mantle cell lymphoma cell proliferation [230,231], and iron deprivation is cytotoxic to malignant B-and T-cells [232,233]. Moreover, in ALL and T-cell lymphoma, DFX displayed synergistic activity with three ALL-specific drugs: dexamethasone, doxorubicin, and L-asparaginase.…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…DFX has also been reported to inhibit mantle cell lymphoma cell proliferation [230,231], and iron deprivation is cytotoxic to malignant B-and T-cells [232,233]. Moreover, in ALL and T-cell lymphoma, DFX displayed synergistic activity with three ALL-specific drugs: dexamethasone, doxorubicin, and L-asparaginase.…”
Section: Iron Chelatorsmentioning
confidence: 99%
“…Since accumulated studies have reported that the antineoplastic efficacy of iron chelators, such as deferoxamine and deferasirox, is caused by G1 arrest followed by p21-triggered apoptosis [30][31][32][33][34][35][36][37][38][39], the cell death induced by PPMX-T003-mediated specific TfR1 blockage in ANKL is unique. Further investigation of the mechanisms, including iron sensing, iron metabolism, and iron cellular distribution, is needed to clarify the differences in cell cycle regulation between iron chelation and specific TfR1 inhibition.…”
Section: Discussionmentioning
confidence: 99%